IMPROVING STUDENTS' SPEAKING SKILLS THROUGH CARTOON MEDIA: A CLASSROOM ACTION RESEARCH AT AN INDONESIAN ELEMENTARY SCHOOL - Jaisy Yasmin Alphariyadi; Lusiana Suciati Dewi; Muhammad Anjar Nugraha (Bajang Institute, 2026)
This study investigates the effectiveness of cartoon media in improving the English-speaking skills of sixth-grade students at an elementary school in Subang, Indonesia. Employing a Classroom Action Research (PTK) design following the Kemmis and McTaggart model, the research was conducted across two cycles, each comprising planning, action, observation, and reflection phases. Data were collected through pre- and post-tests assessed via a speaking rubric (pronunciation, fluency, vocabulary, and grammar), classroom field notes, semi-structured interviews, and documentation. In Cycle 1, despite increased classroom participation, the post-test mean score declined from 60 to 54, attributable to unfamiliar vocabulary and persistent speaking anxiety. Informed by this reflection, Cycle 2 incorporated vocabulary pre-teaching and dubbing activities, resulting in a substantial improvement: the post-test mean rose to 64, with 76% of students reaching the mastery threshold of 70 or above, surpassing the predetermined 75% success criterion. Qualitative data corroborated these gains, with students reporting reduced anxiety and increased enjoyment when learning through cartoon-based activities. The findings support Krashen's affective filter hypothesis and Mayer's Cognitive Theory of Multimedia Learning, suggesting that cartoon media can serve as a low-cost, engaging, and pedagogically effective tool for developing oral communicative competence among young EFL learners.